2022
DOI: 10.1155/2022/7343412
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Multichip Analysis and WGCNA Identify Potential Diagnostic Markers in the Pathogenesis of ST‐Elevation Myocardial Infarction

Abstract: Background. ST-elevation myocardial infarction (STEMI) is a myocardial infarction (MI) with ST-segment exaltation of electrocardiogram (ECG) caused by vascular occlusion of the epicardium. However, the diagnostic markers of STEMI remain little. Methods. STEMI raw microarray data are acquired from the Gene Expression Omnibus (GEO) database. Based on GSE60993 and GSE61144, differentially expressed genes (DEGs) are verified via R software, and key modules associated with pathological state of STEMI are verified b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Therefore, the research on NSTEMI/STEMI-related genes may improve the diagnosis and treatment strategies. Liang et al reported the differentially expressed genes (DEGs) for STEMI by analyzing two datasets (GSE60993, and GSE61144), and focused on immune cell infiltration 28 . However, these datasets were originally analyzed and recorded by Park et al in the GEO database 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the research on NSTEMI/STEMI-related genes may improve the diagnosis and treatment strategies. Liang et al reported the differentially expressed genes (DEGs) for STEMI by analyzing two datasets (GSE60993, and GSE61144), and focused on immune cell infiltration 28 . However, these datasets were originally analyzed and recorded by Park et al in the GEO database 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The emergence of high-throughput omics data and the development of bioinformatics have revealed a large number of potential biomarkers and patterns. Liang obtained transcriptomic datasets of ST-elevation myocardial infarction from public databases, validated key modules related to STEMI pathological status by weighted gene co-expression network analysis (WGCNA), and identified and analysed the diagnostic markers ALOX5AP and BST1 by LASSO and SVM-RFE algorithms [ 22 ]. Moreover, ARG2, MAP4K5 and TSTA3 were identified as diagnostic markers of SONFH by support vector machine-recursive feature elimination (SVM-RFE), WGCNA, last absolute shrinkage and selection operator (LASSO) logistic regression and random forest (RF) algorithms, and further validated by qRT-PCR [ 23 ].…”
Section: Introductionmentioning
confidence: 99%